(untitled) (The Research of Medical Science Review, 2025)
There is an increasing value of natural products in age-related macular degeneration (AMD). This study evaluates the association of different Natural products and development of AMD. online medical data bases like PubMed, web of science and Google Scholar with keywords as “AMD”, “Age-related Macular Degeneration”, “Natural Products”, “food supplements”, “traditional herbal medicine”, “health supplements”, literature from 2000 to March 2020 were searched. Limited case sets, commentaries, Abstracts of cases or individual opinions are omitted, although case-controlled experiments, population-based analyses, and meta-analysis were reviewed. Often subject to strong research concerns is vitamin B and extractions of wolfberry, gingko biloba, and berry anthocyanins, but no study with statistical confirmation has been found in this study to suggest yet. The first large-scale randomised controlled scientific trial named “Age-related Eye diseases Study” (AREDS) shows benefits of AREDS vitamin “C, E, beta-carotene” and “copper zinc” in minimizing possible advancement to severe AMD in patients with moderate AMD or severe AMD in one eye.